ANALISIS PENGARUH WORD OF MOUTH, LOKASI, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN JASA BENGKEL SEPEDA MOTOR CAHYA RIZKY MOTOR (Survei pada Pengguna Bengkel Cahya Rizky Motor di Ngringo, Palur) - Dimas Bayu Kuncoro, Edi Wibowo & Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2016)
The purpose of this study was to analyze the significance of (1) the effect of variable Word of Mouth on purchasing decisions services workshop Cahya Rizky Motor in Ngringo, Palur (2) to analyze the significance of the effect of variable locations on purchasing decisions services workshop Cahya Rizky Motor in Ngringo, Palur (3) to analyze the significance of variables influence the quality of service to the purchasing decision Cahya workshop services Rizky Motor in Ngringo, Palur. The population of this research are all service user at a motorcycle shop and grab a sample of 70 respondents. Data collection technique used questionnaire that through stages of testing the validity and reliability first. Test requirements regression using classic assumption test. Data were analyzed using hypothesis testing. The conclusion of each of these hypotheses indicate that (1) Variable Word of Mouth significantly influence purchasing decisions workshop services Cahya Rizky Motor in Ngringo, Palur. It is shown with p value 0,021 < 0,05 (2) Variable locations significantly influence purchasing decisions workshop services Cahya Rizky Motor in Ngringo, Palur. It is shown with p value 0,000 < 0,05 (3) Variable quality of service significantly influence purchasing decisions workshop services Cahya Rizky Motor in Ngringo, Palur. It is shown with p value 0,000 < 0,05.Keywords: word of mouth, location, quality of service, purchasing decisions.